QOL-21. THE EFFECTS OF RADIATION ON COGNITIVE SCORES IN PEDIATRIC PATIENTS WITH MEDULLOBLASTOMA. Issue 2 (22nd June 2018) - Mazzone, Subha; McElroy, Sara; Mayes, Sunnye; Scott, Jim; Anderson, Michael; McNall-Knapp, Rene
Abstract: BACKGROUND: Medulloblastoma is treated with radiation therapy but causes late effects including decreased cognitive function (domains of processing speed (PSI) and working memory (WMI) particularly affected). Compared to photon radiation (XRT), proton radiation (PBRT) may decrease these risks; however prior studies assessing IQ (FSIQ) found no difference between the two groups. Specific domains of PSI or WMI have not been assessed. Similarly patients who receive tumor bed boost (TBB) compared to posterior fossa boost (PFB) may also fare better cognitively. OBJECTIVE: To compare cognitive scores in medulloblastoma based on type of radiation and boost radiation. METHODS: A retrospective single institution review of >300 medulloblastoma patients treated over the last 20 years. RESULTS: 15 patients with medulloblastoma received radiation and had cognitive testing. 10 patients received XRT and 5 patients received PBRT. 8 patients received TBB and 7 received PFB. Percentile scores in WMI, PSI and FSIQ were compared between PBRT vs. XRT patients and TBB vs. PFB patients. There were no statistical differences in WMI, PSI and FSIQ in the PBRT vs. XRT group (p-values 0.24, 0.13, 0.17) or the TBB vs. PFB group (p-values 0.46, 1.00, 0.85). CONCLUSION: Our data suggests a non-statistical, but potentially clinically significant trend towards superior scores in PSI in the PBRT vs. XRT group (Mean PSI 5.67 vs 23.4, p=0.13). This suggests a clinical benefit to limiting radiation exposure. A larger multi-institutional study would further delineate potential differences.